(untitled) (Medico Legal Update, 2020)
Introduction: The research ethics plays a very vital role in the collection, analysis, reporting and publication of details about research subjects, in particular active acceptance of participant’s right to privacy, confidentiality and the informed consent of the participant. Aims: To assess the Knowledge, awareness and attitudes about research ethics among the faculty and students of medical and dental colleges and the requirement for a regular teaching about research ethics among the faculty and students of medical and dental colleges. Materials and Method: A cross-sectional study was conducted by assessing the responses to 39 selected basic questions regarding Knowledge, awareness and attitudes about research ethics among a total of 415 faculty members and post graduate students of the medical and dental institutions in Mysore city of Karnataka state. The online questionnaire was created by using Google forms. The questionnaire was made into 5 categories. Chi-square tests was used to determine, in bivariate analyses, the association of each of the independent variables. The students t-test was done to assess the respondents scores on the 5-point Likert scale ranging from 1 to 5. The average of their scores were compared among the various variable like their specialty and academic position by using the ANOVA test. Results: A total of 415 responses were obtained from the participants of the study. The response tabulated under various sections clearly showed deficiency in the understanding of research ethics. The P value was kept at 0.05 for this study. Conclusion: The participants of the questionnaire survey showed that the institutional ethics committees would be very useful for promoting health research and are imperative for appraisal of the health research projects. The requirement for a regular teaching about research ethics among the faculty and students of medical and dental colleges is very important. Further study in this area is very much needed.